(untitled) (Medico Legal Update, 2020)
A study to assess depression, anxiety, loneliness and internet addiction among college students using internet in selected colleges, Chennai. Majority of the participants were males, were 20 years old, residing in urban community, used their mobile for internet services, used internet first time in the school, spent more than 4 hrs/day on internet, spend Rs. 300/- per month and use the internet for study, online purchase,whats app & face book, you tube. Majority of the participants had mild level of internet addiction. Equal number of participants had mild, borderline and moderate level of depression (16.3% each). Minority of them reported extreme depression. Majority of the participants had mild anxiety and minority had severe anxiety. Majority of the participants had mild level of loneliness and minority had moderate level of loneliness. Source of internet, browsing duration/day and amount spent for the internet are significantly associated with internet addiction. Browsing duration/day is significantly associated with depression.